2009
DOI: 10.1016/j.envpol.2009.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of scalp hair as indicator of human exposure to heavy metals in an electronic waste recycling area

Abstract: Human scalp hair samples can be used to indicate environmental and occupational exposure of heavy metals due to intensive electronic waste recycling activities. a r t i c l e i n f o a b s t r a c tScalp hair samples were collected at an electronic waste (e-waste) recycling area and analyzed for trace elements and heavy metals. Elevated levels were found for Cu and Pb with geometric means (GMs) at 39.8 and 49.5 mg/g, and the levels of all elements were found in the rank order Pb > Cu [ Mn > Ba > Cr > Ni > Cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
96
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(125 citation statements)
references
References 29 publications
8
96
4
1
Order By: Relevance
“…Agricultural soil contamination with HMs had become a serious environmental problem because it poses a serious threat to human health by entering into food chains and to environmental security by washing into surface water by rain and leaching into shallow groundwater (Shen and Chen, 2000;Romic and Romic, 2003). Cadmium (Cd) is one of the toxic HMs that was used widely in the electrical and electronic industry, and they were most widely detected in e-waste contaminated surroundings (Shen et al, 2008;Guo et al, 2009;Wang et al, 2009;Chen et al, 2010). Therefore, it is necessary to quantify the spatial characteristics of HM in agricultural soils and evaluate the threat of toxic HMs in topsoils to shallow groundwater by leaching in order to be able to formulate a policy to control or eliminate Cd pollution and ensure shallow groundwater safety.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural soil contamination with HMs had become a serious environmental problem because it poses a serious threat to human health by entering into food chains and to environmental security by washing into surface water by rain and leaching into shallow groundwater (Shen and Chen, 2000;Romic and Romic, 2003). Cadmium (Cd) is one of the toxic HMs that was used widely in the electrical and electronic industry, and they were most widely detected in e-waste contaminated surroundings (Shen et al, 2008;Guo et al, 2009;Wang et al, 2009;Chen et al, 2010). Therefore, it is necessary to quantify the spatial characteristics of HM in agricultural soils and evaluate the threat of toxic HMs in topsoils to shallow groundwater by leaching in order to be able to formulate a policy to control or eliminate Cd pollution and ensure shallow groundwater safety.…”
Section: Introductionmentioning
confidence: 99%
“…Hair has been used as a bioindicator for human exposure to drugs abuse or metals (Pragst and Balikova, 2006;Wang et al, 2009). Recently the idea of using hair analysis for assessing exposure to POPs has been explored (D 0 Havé et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elements in hair have also been reported to be a reliable and convenient indicator of environmental adaption, and environmental pollution [5][6][7]. These studies indicated that higher levels of Cu, Pb, Zn, and many other elements in human hair were found in the areas contaminated by heavy metals compared with the other areas [8][9][10][11].…”
Section: Introductionmentioning
confidence: 61%